Inicjatywa naddunajska Unii Europejskiej. Nowy plan Tardieu? - Koźbiał, Krzysztof (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2012)
The new EU Strategy for the Danube Region came into force on April 13, 2011. Referred to as the Danube Initiative it assumes cooperation within a greater European macro-region covering 1,080,000 km2 with over 115,000,000 inhabitants. The region encompasses as many as fourteen states, six of which are currently outside the European Union. Brussels aims to develop an improved transportation network inside the region by means of water, rail and roads, achieve stronger commitment to environmental protection, contribute to increased prosperity in this part of Europe and improve institutional cooperation in order to fight corruption and organized crime. Achieving these challenging goals is to result in increased unification of the region, in particular its less developed territories, with the UE in terms of economy and social development. The implementation of the Danube Initiative does not involve the establishment of any new institutions or resources. The goals are to be achieved by making better use of current measures.
The European Union’s initiative for the Danube region. A new Tardieu Plan?